Arlo and the great big cover-up - Howard, Betsy Childs, 1981- (Crossway, 2020)
"Arlo colors on his wall during naptime, then begins a desperate attempt to hide his disobedience. His mother forgives him. Arlo learns that we cannot hide sin from God, and that confession opens the door to mercy and reconciliation"--